Peningkatan Kompetensi Digital Pendidik Melalui Pelatihan Artificial Intelligence (AI) PAUD Aba Percontohan Bojonegoro - Putri, Berliana Fairelia; Masniyah, Hannik; Rahmawati, Adelia; Septi Putri, Adinda Balqis; Ratu Keylla, Citra Puspita; Nisa, Khoirun; Susilo, Heryanto; Tri 'Ulya Qodriyati (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2025)
Abstract: Digital transformation in the education sector requires teachers to master the latest technology, including artificial intelligence (AI). Early childhood education as a basis for learning requires teachers who can adapt to technological advances in order to create innovative and interesting learning experiences for children. However, there are still many PAUD educators who have difficulty integrating digital technology into teaching and learning activities. To meet this need, PAUD ABA Perpilotan Bojonegoro in collaboration with Bojonegoro ICT Volunteers held a training on "Introduction and Utilization of Artificial Intelligence in PAUD Learning" on April 26, 2025. This training aims to improve the digital skills of teachers by understanding the basic concepts of AI, how AI works, the application of generative AI, and the use of various AI-based tools to support the development of teaching materials and learning media. With a composition of 70% practical and 30% theoretical, this training seeks to equip educators with skills appropriate to the 21st century, support educational transformation that is in line with technological developments, and improve the quality of learning in PAUD. Abstrak: Transformasi digital dalam sektor pendidikan mengharuskan para pengajar untuk menguasai teknologi terbaru, termasuk kecerdasan buatan (AI). Pendidikan anak usia dini sebagai dasar pembelajaran memerlukan pengajar yang dapat menyesuaikan diri dengan kemajuan teknologi guna mewujudkan pengalaman belajar  inovatif serta menarik untuk anak-anak. Namun, masih terdapat banyak pendidik PAUD yang mengalami kesulitan dalam mengintegrasikan teknologi digital ke dalam kegiatan belajar mengajar. Untuk memenuhi kebutuhan ini, PAUD ABA Percontohan Bojonegoro bekerja sama dengan Relawan TIK Bojonegoro mengadakan pelatihan "Pengenalan dan Pemanfaatan Kecerdasan Buatan dalam Pembelajaran PAUD" pada tanggal 26 April 2025. Pelatihan ini bertujuan untuk meningkatkan kemampuan digital para pengajar dengan memahami konsep dasar AI, cara kerja AI, penerapan AI generatif, serta penggunaan berbagai alat berbasis AI untuk mendukung pengembangan materi ajar dan media pembelajaran. Dengan komposisi 70% praktis dan 30% teori, pelatihan ini berusaha membekali para pendidik dengan keterampilan yang sesuai di abad ke-21, mendukung transformasi pendidikan yang selaras dengan perkembangan teknologi, dan meningkatkan mutu pembelajaran di PAUD.